Staff and school development: implications for teacher productivity, motivation and commitment - Muzvidziwa, Irene (University of Zimbabwe Publications, 2016)
The aim of this article is to demonstrate the inter-relatedness of the concepts of staff development, school development and Human Factor (HF) development. The three concepts are clearly linked to school effectiveness and school improvement. The first part of the essay explains what staff development, school development and the HF mean. The second part seeks to explore the educational significance of the relationship between the three concepts.The third section discusses how school leaders might promote both staff and school development in the context of HF development in a primary school, and finally, the fourth section discusses issues that need to be considered when implementing staff and school development programmes.